Applying n-dimensional hypervolumes for species delimitation: unexpected molecular, morphological, and ecological diversity in the Leaf-Toed Gecko Phyllodactylus reissii Peters, 1862 (Squamata: Phyllodactylidae) from northern Peru - Koch, Claudia; Flecks, Morris; Venegas, Pablo J.; Bialke, Patrick; Valverde, Sebastian; Rödder, Dennis (Zootaxa, 2016)
An integrative taxonomic approach based on morphology, molecular analyses, and climatic niche modeling was used to uncover cryptic diversity in the phyllodactylid gecko species Phyllodactylus reissii. At least three distinct species could be identified among the examined specimens from southern Ecuador and northern Peru. Phyllodactylus magister, described by Noble (1924) from arid Andean valleys of the Chinchipe and Marañón rivers in the Peruvian Department of Cajamarca and synonymized with P. reissii by Dixon & Huey (1970) is elevated from synonymy and a detailed redescription is provided. A new species of the genus Phyllodactylus from the Andean dry forest of the southern Marañón valley is identified and described herein. Phyllodactylus pachamama sp. nov. is differentiated from other South American congeners on the basis of mtDNA sequence divergence, morphological characters, and differences in the realized climatic niche. At least in Peru, P. reissii seems to primarily inhabit the northern coastal region west of the Andes, while the inter-Andean area along the Río Marañón and its tributaries seems to be inhabited mostly by other species of the genus, which are endemic to this area. The Andean valleys are underestimated in terms of biodiversity and lack thorough investigation and conservation actions.